2012
DOI: 10.1111/j.1365-2389.2012.01494.x
|View full text |Cite
|
Sign up to set email alerts
|

Modelling long‐term carbon dynamics in soils reconstituted with large quantities of organic matter

Abstract: In urban conditions, the widescale availability of organic matter to be recycled and the necessity for soil reconstitution (Technosol) has led to the input of very large quantities of organic matter (up to 50% v/v). The long‐term degradation of these large quantities of organic matter in the soil is not well known. We monitored, over a 60‐month period, the total carbon (C) content and the particulate and biochemical fractions of reconstituted soils placed in 600‐litre boxes under natural conditions. The top la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 28 publications
(57 reference statements)
2
15
0
Order By: Relevance
“…The organic carbon ( OrgC ) content of the compost treatments was modelled using the simulation proposed by Vidal‐Beaudet et al . () for the same experimental set‐up.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…The organic carbon ( OrgC ) content of the compost treatments was modelled using the simulation proposed by Vidal‐Beaudet et al . () for the same experimental set‐up.…”
Section: Methodsmentioning
confidence: 97%
“…Organic carbon content (OrgC): this was determined (three replicates for each sample) by dry combustion using an elemental analyzer (Thermoquest FlashEA1112 â , Thermo Fisher Scientific, Waltham, MA, USA). The organic carbon (OrgC) content of the compost treatments was modelled using the simulation proposed by Vidal-Beaudet et al (2012b) for the same experimental set-up.…”
Section: Analysesmentioning
confidence: 99%
“…In the urban context, soil age, based on well-documented historical periods, was defined according to the date of soil settlement but the "real" date of birth was difficult to estimate because most of soils were originally formed by geomorphic processes (Gobat et al 2013). Several authors also reported an acceleration of soil pedogenetic processes due to human activities in urban soils (Strehler 1997;Baumgartl 1998;Vidal-Beaudet et al 2012). This trend can be first explained by the nature of the deposit.…”
Section: Urban and Alluvial Soil Differencesmentioning
confidence: 99%
“…Second, most recent human-made soils (1970JR, 1995HR, 2010PR and 1995HR) were made with different organic amendments such as com-post. The effects of the input of "anthropic" materials (organic or mineral) on soil processes are little known (Vidal-Beaudet et al 2012) although Strehler (1997) showed a rapid organic matter turnover in urban soils compared to natural soils.…”
Section: Urban and Alluvial Soil Differencesmentioning
confidence: 99%
See 1 more Smart Citation